Photoinduced double perfluoroalkylation of methylacenes. Issue 24 (15th June 2016) - Nogami, Emiko; Washimi, Yuri; Yamazaki, Takashi; Kubota, Toshio; Yajima, Tomoko
Graphical abstract: Highlights: Novel photoinduced double perfluoroalkylation of methylacenes has been described. The perfluoroalkylations occurred at the methyl and its para position. The product was a mixture of the aromatic compound and its tautomer. Steric repulsion of fluorine and hydrogen determines the product ratios. Abstract: Novel photoinduced double perfluoroalkylation of methylacenes has been described. The reaction proceeded with appropriately substituted methylacenes to produce a mixture of the expected aromatic compounds with Rf groups both at the methyl and its para position as well as the corresponding nonaromatic tautomers. Steric repulsive interaction of fluorine atoms in perfluoroalkyl groups with hydrogen atoms at the peri positions would be the most significant factor for control of ratios of these products.